A tritrophic plant-insect-pathogen system used to develop a closely linked Rag2 and Rsv1-h recombinant haplotype in double-resistant soybean germplasm - Posadas, Luis G.; Baldin, Edson LL [UNESP]; Marchi-Werle, Lia; Heng-Moss, Tiffany M.; Speck, Scott; Stupar, Robert M.; Eskridge, Kent M.; Graef, George L. (Springer Nature, 2025)
BackgroundThe colocalization of two resistance (R) genes on chromosome 13 of soybean (Glycine max (L.) Merrill) that confer resistance against the soybean aphid (Aphis glycines) and soybean mosaic virus (SMV) gives rise to a very unique R-avr tritrophic incompatible interaction system that goes across biological kingdoms. In this tritrophic system, the insect is the only natural vector of the virus and soybean is a host-plant for both pests/pathogen. The almost unavoidable co-evolution of pathogen-vector with that of the R-genes in soybean plants through an endless arms race to avoid each other’s defense-attack mechanisms raises interesting questions. The objectives of this work were to (i) develop double-resistant recombinant inbred lines (RILs) with a Rag2-Rsv1-h gene haplotype in coupling phase using resistance alleles from two different genetic sources (PI 243540 (Rag2) and Suweon 97 (Rsv1-h)), (ii) confirm phenotypically the resistant reaction against both pests in double-resistant RILs, and (iii) dissect the Rag2-Rsv1-h region with molecular markers and investigate the potential for structural variation.ResultsWe observed a recombination event in identified double-resistant F3:5 RILs in a region of chromosome 13 ca. 21 kb long (between positions 30,297,227 and 30,318,949 in Wm82.a2.v1) that lies between the reported locations of the Rsv1-h and Rag2 genes (29,815,463--29,912,369 and 30,412,581--30,466,533 intervals, respectively, based on Wm82.a2.v1), indicating the double-resistant haplotype is in coupling phase. The tight LD estimates obtained between haplotype markers underscored the physical proximity of the two resistance genes. Only 10 recombinant haplotype classes (excluding double heterozygotes) were observed among the 51 that were possible with a four loci haplotype. The 10 recombinant classes represented 15 out of 192 screened individuals. A joint SMV-aphid phenotypic greenhouse screen allowed us to identify the best aphid biotype 1 and SMV-G1, double resistant haplotype class in recombinant progeny. Our molecular marker results agree with previous fine-mapping reports and preclude the presence of resistance genes other than Rag2 and Rsv1-h in double-resistant RILs. A comparative genomic hybridization analysis revealed no obvious structural variants in the region.ConclusionsTo our knowledge, this is the first report of double-resistant Rag2-Rsv1-h soybean RILs that used a plant-insect-pathogen tritrophic system for germplasm enhancement. The co-occurrence of Rag and Rsv genes in a region that clusters resistance genes on chromosome 13 may be a unique feature of domesticated soybean. The recombinant genotypes will be useful in breeding to develop soybean cultivars with resistance to both the vector and the virus. The parental and recombinant genotypes may be helpful in future studies to elucidate interesting evolutionary questions regarding vector, host, and virus tritrophic systems.